Real-world efficacy and safety of letermovir versus ganciclovir prophylaxis in adolescent patients undergoing allogenic hematopoietic stem cell transplantation: a single center observational study - Xu, Ziwei; Lu, Xuan; Wang, Huafang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesTo compare the efficacy and safety of letermovir and ganciclovir for cytomegalovirus (CMV) prophylaxis in adolescent patients (aged 14-17 years) undergoing allogenic hematopoietic stem cell transplantation (allo-HSCT).MethodsThis observational and single-center study collected data from February 2023 and April 2024.ResultsThe cumulative incidence of CMV DNAemia following HSCT was 44.4% in the letermovir group (n=20) and 66.3% in the control group (n=32) receiving ganciclovir. Notably, the cumulative incidence of clinically significant CMV infection (csCMVi) was significantly reduced in the letermovir group compared with control patients (11.0% vs 41.3%, p=0.021). Among patients diagnosed with grades II-IV acute graft-versus-host disease (aGVHD), a significantly lower proportion of individuals in the letermovir group presented CMV DNAemia than in the control group (20.0% vs 73.3%, p=0.013). The common adverse events observed in the letermovir group were aGVHD (60.0%), diarrhea (25.0%), and nausea (15.0%). Leukopenia was reported in only one patient, and did not necessitate an adjustment of letermovir dosage.ConclusionsIn this single-center real-world study, letermovir exhibited a favourable efficacy and safety profile for CMV prophylaxis in adolescent patients undergoing HSCT. However, further prospective multi-center studies are warranted to validate our conclusion in adolescent patients.